Enhanced bioactivity and interfacial bonding strength of Ti3Zr2Sn3Mo25Nb alloy through graded porosity and surface bioactivation. (20th February 2022) - Yu, Sen; Yu, Zhe; Guo, Dagang; Zhu, Hui; Zhang, Minghua; Han, Jianye; Yu, Zhentao; Cao, Yemin; Wang, Gui
Research highlights: A coating with pores of several microns in diameter is created through micro arc oxidation (MAO) on the surface of the gradient porous Ti3 Zr2 Sn3 Mo25 Nb alloy with larger pores of hundreds microns fabricated from powder sintering on the solid alloyed core. The MAO treatment in an electrolyte containing Ca and P enables the secondary microporous coating contained hydroxyapatite (HA), and the bone morphogenetic protein-2 (BMP-2) was further loaded on to the coating (HA+BMP). Both HA and BMP-2 on the surface and inside pores significantly activate the bioactive of the alloy by promoting the formation of new bone tissue on the surface and stimulating new bone tissue to growth into the gradient porous Ti3Zr2Sn3Mo25Nb alloy. The interfacial shear strength of the coatings with HA or HA+BMP is higher than that of the coating without both HA or BMP-2 at all time after implantation, the strength in the HA+BMP coating is highest in the three coatings and is about three times of the strength of the CPT sample in all the testing implantation intervals. Abstract: The gradient porous Ti3Zr2Sn3Mo25Nb (TLM) alloy rods were fabricated through sintering the alloyed powder to a solid core. The porous sample was then modified by a Micro Arc Oxidation (MAO) treatment in an electrolyte containing calcium and phosphate, a hydrothermal treatment enabled secondary microporous hydroxyapatite (HA) coating, and a further bone morphogenetic protein-2 (BMP-2) loading treatment through immersion and freeze-drying. The treatment led to an orderly secondary microporous coating containing HA nano-particles and evenly distributed BMP-2 in the porous coatings. As a result, osteoblasts could adhere and grow well on the coatings with a high cell adhesion rate and cell functional activity. The in-situ shear testing indicated that the interfacial strength had been enhanced significantly. Improvement of the bond formation and osseointegration with the titanium implant is attributed to increased surface area for the cell to attach, creating voids for the cell to grow in, and activating titanium surface by introducing bioactive ingredients such as HA and BMP-2. Graphical abstract: Image, graphical abstract